Household type load's effects on photovoltaic systems - (:unkn) unknown (My University, 2008)
The solar energy is one of the most important energy sources available because, besides the fact that it is not polluting the enviromnent and it helps to the reduction of green house effect, it is free of charge and it can be easily converted to other forms of energy. Clean and renewable energy production is getting more attractive due to global warming, environmental factors and decrease in conventional energy sources. Photovoltaic cells will be a good alternative against the conventional energy sources in the near future, with their decreasing costs and increasing efficiencies. Photovoltaic cells (PV) are exposed to a lot of various loads depending on their increasing usage areas. Among the energy expenses for a building, the lighting system can contribute up to 50% of the total electrical consumption, and especially large quantities of energy are used in schools and office buildings. For that reason lighting devices are important energy consuming units in our daily life. In this study different load effects on PV cells are examined experimentally. D.C. and A.C. load behaviors are analyzed in switching and in steady state regime and their power-time curves are obtained for the demand of system power. Negative effects of the inverter circuit, which is used for feeding A.C. loads on the system, are expressed experimentally.
Keywords: A.C. loads; Compact fluorescent lamp; D.C. loads; Photovoltaic system; Power LED